Assessing state partner use of the Model Aquatic Health Code (MAHC): A cross comparison of five states with varying degrees of self-reported adoption status. - Patrick Vander Kelen; Joseph P Laco; Shannon McClenahan; Christopher Fletcher; Brian Hubbard (PLOS Water)
Despite the development of the Model Aquatic Health Code (MAHC), U.S. public health departments and aquatics agencies face obstacles in incorporating this guidance into their pool codes. A cross comparison of five state pool codes with the MAHC was conducted to quantify MAHC incorporation into these state codes. The proportion of MAHC code agreement with state codes in this study had a range of 14%-86%. Only 2% of all the MAHC codes available were present in all five state codes, conversely, 12% of the MAHC codes were not found in any state. These differences in code agreement highlight the challenge of measuring MAHC effectiveness at the national level. To improve aquatic safety at a national level, a potential solution is development and use of common core elements in state and local pool codes. Once there is a basis for code comparisons across states, public health programs can investigate whether core MAHC codes result in reduced waterborne illness outbreaks, drowning incidents, injuries from pool chemicals, health outcomes from exposure to disinfection by-products, and swimming-related emergency department visits.